Characterization of particle number size distribution and new particle formation in Southern China - Huang, X. F.; C. Wang; Peng, J. F.; He, L. Y.; Cao, L. M.; Zhu, Q; J. Cui; ZJ Wu; Hu, M. (Journal of Environmental Sciences, 2017)
Knowledge of particle number size distribution (PND) and new particle formation (NPF) events in Southern China is essential for mitigation strategies related to submicron particles and their effects on regional air quality, haze, and human health. In this study, seven field measurement campaigns were conducted from December 2013 to May 2015 using a scanning mobility particle sizer (SMPS) at four sites in Southern China, including three urban sites and one background site. Particles were measured in the size range of 15-615 nm, and the median particle number concentrations (PNCs) were found to vary in the range of 0.3 x 10(4)-2.2 x 10(4) cm(-3) at the urban sites and were approximately 0.2 x 10(4) cm(-3) at the background site. The peak diameters at the different sites varied largely from 22 to 102 nm. The PNCs in the Aitken mode (25-100 nm) at the urban sites were up to 10 times higher than they were at the background site, indicating large primary emissions from traffic at the urban sites. The diurnal variations of PNCs were significantly influenced by both rush hour traffic at the urbansites and NPF events. The frequencies of NPF events at the different siteswere 0%-30%, with the highest frequency occurring at an urban site during autumn. With higher SO2 concentrations and higher ambient temperatures being necessary, NPF at the urban site was found to bemore influenced by atmospheric oxidizing capability, while NPF at the background site was limited by the condensation sink. This study provides a unique dataset of particle number and size information in various environments in Southern China, which can help understand the sources, formation, and the climate forcing of aerosols in this quickly developing region, as well as help constrain and validate NPF modeling. (C) 2016 The Research Center for Eco-Environmental Sciences, Chinese Academy of Sciences. Published by Elsevier B.V.
Keywords: aerosol nucleation; air pollution; atmosphere; boundary-layer; cities; distribution (PND); Environmental Sciences & Ecology; exhaust; mixing state; nanoparticles; New particle formation (NPF); Particle number size; particulate matter; region; Scanningmobility particle sizer (SMPS); southern china; urban